Inhibition of endoplasmic reticulum stress is involved in the neuroprotective effect of aFGF in neonatal hypoxic-ischaemic brain injury - Hu, Yingying (Oncotarget, 2017)
Acidic fibroblast growth factor (aFGF) has been shown to exert neuroprotective effects in experimental models and human patients. In this study, we investigated whether aFGF intranasal-treatment protected against neonatal hypoxic-ischaemic brain injury and evaluated the role of endoplasmic reticulum stress. The Rice-Vannucci model of neonatal hypoxic-ischaemic brain injury was used in 7-day-old rats, which were subjected to unilateral carotid artery ligation followed by 2.5 h of hypoxia. Intranasal aFGF or vehicle was administered immediately after hypoxic-ischaemic injury (100 ng/g) and then twice a day for 1 week to evaluate the long-term effects. Here we reported that intranasal-treatment with aFGF significantly reduced hypoxic-ischaemic brain infarct volumes and the protective effects were at least partially via inhibiting endoplasmic reticulum stress. In addition, aFGF exerted long-term neuroprotective effects against brain atrophy and neuron loss at 7-day after injury. Our data indicate that therapeutic strategies targeting endoplasmic reticulum stress may be promising to the treatment of neonatal hypoxic-ischaemic brain injury.